A Critical Examination of Explorative And Exploitative Innovation in the Smartphone Industry - Akhtar, Jamil (2010)
Organisations need to balance gains from the present through exploitative innovation as well as those from the future through explorative innovation. However, the means of achieving this balance are debated. This paper evaluates alternative conceptualisations of exploratory and exploitative innovation by challenging the assumptions within this body of literature. Utilising two case studies within the smartphone industry, it finds evidence for innovation capabilities and provides insight on how these are created, developed and utilised. It finds support for the fundamental tension between exploratory and exploitative innovation, with the cases revealing ways to resolve this tension. Differing from current definitions of ambidexterity, it highlights that organisations are able to benefit from both innovation capabilities by utilising the market mechanism. The findings offer interesting implications to facilitate organisational comprehension and application of innovation capabilities.